New localities of Orobanche bartlingii Griseb. in the Silesian-Cracow Upland as a result of the spread of Libanotis pyrenaica (L.) Bourg. due to the changes in land use - Babczyńska-Sendek, Beata; Błońska, Agnieszka; Skowronek, Izabela (Biodiversity: Research and Conservation, 2015)
Human activity is a factor strongly influencing the current state of vegetation. The abandonment of traditional land use enables uncontrolled secondary succession. Libanotis pyrenaica, a host plant for Orobanche bartlingii, is a great example of species that spread as a result of this process, especially in the area of the Silesian-Cracow Upland. The aim of this study is to show that the expansion of L. pyrenaica caused by changes in land use promotes spreading of O. bartlingii - a species rare in Poland and Europe. During the field research conducted in the last decade, further localities of O. bartlingii were found. The gathered data were summarized to supplement the known distribution of the species and to present floristic and ecological characteristics of the phytocenoses with the participation of L. pyrenaica and O. bartlingii.